Diet Reduce Apnea Hypopnea Index (Ahi) Score in Obstructive Sleep Apnea Patient: Systematic Review and Meta-analysis - Adella Bintang Saputri; Nindya Shinta Rumastika; Muhammad Afiful Jauhani; Wiwien Sugih Utami; Jauhar Firdaus (Faculty of Medicine, Universitas Jember, 2024)
Obstructive sleep apnea (OSA) is a breathing disorder during sleep that can cause obstruction to the flow of breathing with characteristics such as collapse of the upper airway which can cause breathing to stop, either completely (apnea) or partial (hypopnea). Based on a study of taxi drivers in Jakarta, it was found that 52,5% of the sample had OSA. One of the main factors for OSA is obesity. Based on The American Academy of Sleep Medicine (AASM) recommends weight loss through lifestyle modifications (eg applying diet) as a treatment option for AHI improvement in OSA. The purpose of writing this article is to prove that adopting a diet can reduce the apnea hypopnea index (AHI) of OSA. The method in this study is a systematic review and meta-analysis using secondary data derived from PubMed, Science Direct, and Springer databases published from 2019 to 2022.. A total of six randomized controlled trial (RCT) articles were investigated by meta-analysis The weighted mean difference in AHI (-6,77 event/d with 95% CI: -13,42 to -0,1) significantly favoured diet over control arms. Based on the results of a systematic review and meta-analysis of six articles, the application of a diet is proven to reduce AHI scores in OSA patients. Keywords: Obstructive sleep apnea, Apnea hypopnea index, Diet